Phosphoric acid concentration affects dentinal MMPs activity. (October 2016) - DeVito-Moraes, A.G.; Francci, C.; Vidal, C.M.P.; Scaffa, P.M.C.; Nesadal, D.; Yamasaki, L.C.; Nicolau, J.; Nascimento, F.D.; Pashley, D.H.; Carrilho, M.R.
Abstract: Objectives: To evaluate whether the concentration of phosphoric acid (PA) has an effect on the proteolytic activity of sound human demineralized dentin. It is hypothesized that the activity of matrix-bound and extracted enzymes depends on the PA concentration used to demineralize dentin. Methods: One-gram aliquots of mid-coronal human dentin powder were demineralized with 1 wt%, 10 wt% and 37 wt% PA. Concentrations of released calcium were measured for each set of demineralization. Extracted MMP-2 was immunologically identified by western blot and its activity was determined by conventional gelatin zymography. Analysis of released hydroxyproline (HYP) and in situ zymography were performed to evaluate the activity of insoluble, bound-matrix enzymes. Results: The amount of released calcium from dentin powder treated with 37 wt% PA was significantly higher (p ≤ 0.05) than that obtained by dentin demineralization with 10 wt% and 1 wt% PA. Expression and activity of endogenous enzymes, extracted from or bound to dentin matrix, were detected for all samples regardless of the PA concentration. However, the expression and activity of extracted MMP-2 were significantly higher when dentin was treated with 10 wt% PA (p < 0.05), followed by 1 wt% and 37 wt% PA. Similarly, the highest concentration of released HYP (i.e. meaning higher percentage of collagen degradation) and the highest activity in in situ zymography were observed when dentin samples were treated with 10 wt% PA (p < 0.05). Conclusions: It was confirmed that PA does not denature endogenous enzymes of dentin matrices, but it may somehow modulate the expression and activity of these enzymes in a concentration-dependent manner. Clinical significance: Endogenous proteases have been identified and suggested to be responsible for the digestion of dentin matrix when activated by the acidic components of dental adhesives. Proteolytic activity of dentinal MMPs showed to be dependent on phosphoric acid concentration. The clinically-used concentration (37%) does not inhibit MMPs activity, but slows it.